(untitled) (Research, Society and Development, 2020)
The purpose of the research was to determine the topics of reading preferred by second-year middle school students of a subsidized private school in the community of El Bosque in Chile. The research approach was quantitative descriptive. The sample corresponded to 118 students in the second year of the educational establishment. The data collection technique was the survey and the collection instrument was the questionnaire. According to the results, teachers promote the participatory and critical attitude to their students with a methodology that includes sharing readings and favoring reading experiences but without reaching the creative level. Students enjoy reading very little and the topics they prefer are sports, books about favorite artists, action stories with young protagonists and comics, however teachers do not look for adequate spaces for them to come into contact with these texts, causing them not to read about other topics and not participate in class.